Essential oil content and components, antioxidant activity and total phenol content of rosemary (Rosmarinus officinalis L.) as affected by harvesting time and drying method - Doozakhdarreh, Seyedeh Fatemeh Khademi (2023)
Harvesting time had a significant effect on the essential oil content of plants, so that the essential oil content of plants harvested at 5 am and 5 pm was significantly higher than plants harvested at 12 noon. At all harvest times, shade dried plants had the highest essential oil content, while the lowest content was obtained in microwave-dried plants. Generally, the highest essential oil content (1.12%) was obtained at 5 am harvest and shade dried plants, followed by 5 pm harvest and shade dried (1.08%), and the lowest essential oil content (0.58%) was obtained at 12 noon harvest and microwave-dried plants (Fig. 1). The number, type and total of identified compounds were varied in the essential oils of plants harvested at different times and drying methods (Table 2). The highest number of identified compounds (27 compounds) was observed in the essential oils of plants harvested at 12 noon and dried in the shade, as well as plants harvested at 5 pm and dried in the oven.